THE METHODOLOGY OF EVALUATION OF THE WORKPLACE DIGITALIZATION LEVEL - Dariia Doroshkevych; Inna Lytvynenko (Green, Blue and Digital Economy Journal, 2021)
The purpose the worldwide increase of the digitalization level and COVID-19 pandemic at the same time lead to a situation in which companies have to adapt to the trend of remote economics and change the working environment of their employees. Methodology. This research aimed at improving the methodology for assessing the level of workplace digitalization and to evaluate the level of workplace digitalization on the example of a company “IT marketing”, taking into account technical and moral factors. Recent years statistics confirms the growth of people working from home and building careers remotely. Increasing the level of mobility and flexibility of personnel, digitization of the workplace, national and gender diversity of staff – all these trends proof that the workforce is a powerful factor for the intensive growth of the whole company. But at the same time the process of workplace’s digitizing requires deep scientific researches. Strengthening the level of security, the presence of digital etiquette, new corporate culture, the moral stress of staff to keep in touch can lead to burnout and reduce employee’s performance and therefore – profitability of enterprises. It is impossible to ignore the trend towards increasing remote economics that is proved by numerous scientific studies. At the same time, sociologists argue that today for the effective functioning of the economy the vector must be shifted from technology to humans. One of the main objectives of the presented research is to identify tools that can increase the level of digitalization of the workplace and at the same time enlarge the efficiency of working staff. These tools should cover all aspects of doing business including customer and employee engagement, accounting and financial transactions, project management and productivity. Thus, the presented article reflects the study of current trends in the socio-economic sphere, the results of which may have an impact on human relations in companies and meet the needs of employees while observance of high level of their work efficiency. Results. The research we used our methodology and evaluated the level of digitalization on the example of company “IT-Marketing”. Practical implications. In the article gave the recommendations to the company’s management how to increase the level of workplace digitalization.